SARS-CoV-2 infection in children and adolescents: a Brazilian experience - Santos, Adriana De Oliveira Ribeiro dos; Lucarevschi, Bianca Rezende; Bajerl, Mariana Hool; Pires, Luara de Oliveira; Ubriaco, Dafny Cristina; Nascimento, Luiz Fernando Costa [UNESP] (FapUNIFESP (SciELO), 2022)
Objective: To describe clinical and epidemiological aspects of children and adolescents infected with the SARS-CoV-2 in the Municipality of Taubate, SP, from March to November 2020. Methods: Cross-sectional study with secondary data obtained from the Epidemiological Surveillance System about confirmed cases in city residents and from medical records of patients who were treated in hospitals in Taubate, aged between 0 and 19 years. Chi-square and Student's t tests were used for comparisons. Results: 677 cases in the studied age range were reported during the study period, corresponding to 10.1% of cases reported in the municipality. The rapid antibody test was the most used to confirm infection, followed by RT-PCR and serology. Symptoms were described in 57.7% of the cases, mainly fever and cough. Diarrhea was associated with age below 4 years, while fever, cough, headache, odynophagia, ageusia, anosmia, myalgia, and dyspnea were associated with an age ranging from 10 to 19 years. In the study period, there were no deaths from COVID-19 of residents of the municipality in the age group from 0 to 19 years. Conclusions: The study was able to identify the proportion of involvement of COVID-19 in children and adolescents in the city, and the disease had a mild evolution. The main symptoms were fever and cough, but mainly diarrhea in younger children, and headache, odynophagia, anosmia, ageusia, and myalgia in adolescents.
Keywords: Adolescent; Children; Coronavirus infections; COVID-19; Pandemics; Pedriatrics